CHEMICAL PROPERTIES OF SOIL IN QUARTZ SAND MINING IN RIAU ISLANDS PRE-RECLAMATION ACTIVITIES: SIFAT KIMIA TANAH PADA TAMBANG PASIR KUARSA DALAM KEGIATAN PRA REKLAMASI KEPULAUAN RIAU - Dita Irwanti Pratiwi; Mohammad Nurcholis (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2023)
It is necessary to figure out the chemical characteristic of soil in the pre-reclaimed land of quartz sand mines in order to find the appropriate and optimal reclamation method applied. A laboratory analysis is then conducted to determine the impact of the causes of decreased soil fertility. This research is conducted at PT. X Kepulauan Riau. The method used for soil sampling is FAO (1976) at a depth of 0-30 cm, with a total of 4 samples, namely sample A, B, C, and D. Sample A, B, and C are used in the XRF (X-Ray Fluorescence) method to determine the chemical compounds contained in the soil, while sample D is used for analyzing the soil chemical characteristic to determine the nutrients contained in the soil. Based on the results of the analysis, the condition of the pre-reclaimed land of quartz sand is classified as infertile. Nutrient levels in the pre-reclaimed land were mostly low, and this is an important factor inhibiting plants from growing at the study site.